Assessing the fairness of the golf handicapping system in the UK - McHale, I. G. (Journal of Sports Sciences, 2010)
In this paper, I examine the properties of the handicapping system in the UK. Using a generalized ordered logistic regression model of hole by hole scores of individuals, simulation was employed to calculate the probability of winning for an individual in stroke play and match play head to heads and also in tournament competitions with multiple entrants. The results suggest that the current handicapping system does not produce equal probabilities of players with different handicaps winning. Specifically, lower handicappers have a higher probability of winning in both stroke play and match play games. Having investigated the possibility of employing scaling factors in order to level these probabilities, I pose the question of the extent to which equal probabilities is in fact a desirable property of a handicapping system.